Efektivitas Biolarvasida Ekstrak Daun Sirsak Dan Serai Wangi Terhadap Larva Nyamuk Aedes aegypti - Sefrinus MD Kolo (Fakultas Pertanian, Universitas Timor, 2018)
This study aims to determine the activity of biolarvasida Annona muricata L leaf extract and Cymbopogon nardus L to Aedes aegypti larvae. The experimental design used was a randomized block design (RAK). Treatment of Annona muricata L leaf extract and Cymbopogon nardus L extract were 750ppm, 1000ppm, 1500ppm, 2000ppm, and 5000ppm with contact time 20min, 45min, 65min, 90min and replication counted 3 times with 15 experiments. To know the effective concentration (LC50), the data were analyzed using Minitab 16 programme. The sample of this research is Annona muricata L leaf taken in community garden of Kefa Selatan Maslete Village, Cymbopogon nardus L taken in Oenenu Village. Aedes aegypti larvae were taken at a water shelter at BTN Naiola Village, South Bikomi District. The results showed that Annona muricata L leaf extract and lemon grass have an effective killing effect against Aedes aegypti larvae. A more effective extract in killing mosquito larvae is Annona muricata L leaf extract compared to the extract of Cymbopogon nardus L fragrance seen in the percentage of larval deaths. The LC50 score reached 214 in the 90th minute. This indicates that enough toxicity. Effective concentration is found at concentration 2000ppm with contact time for 90 minutes with protection power of 96.66%.